2004
DOI: 10.1073/pnas.0402993101
|View full text |Cite
|
Sign up to set email alerts
|

HER-2 gene amplification can be acquired as breast cancer progresses

Abstract: Amplification and overexpression of the HER-2 oncogene in breast cancer is felt to be stable over the course of disease and concordant between primary tumor and metastases. Therefore, patients with HER-2-negative primary tumors rarely will receive anti-Her-2 antibody (trastuzumab, Herceptin) therapy. A very sensitive blood test was used to capture circulating tumor cells (CTCs) and evaluate their HER-2 gene status by fluorescence in situ hybridization. The HER-2 status of the primary tumor and corresponding CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
368
1
19

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 488 publications
(403 citation statements)
references
References 18 publications
15
368
1
19
Order By: Relevance
“…Consistent with our prior results (19), five formerly HER-2 Ϫ cases acquired HER-2 ϩ CTCs upon recurrence or progression. Their patterns of HER-2 distribution were similar to those whose primary tumor was HER-2 ϩ .…”
Section: Correlation Of Her-2 Gene Status Between Ctcs and Primary Tusupporting
confidence: 81%
See 2 more Smart Citations
“…Consistent with our prior results (19), five formerly HER-2 Ϫ cases acquired HER-2 ϩ CTCs upon recurrence or progression. Their patterns of HER-2 distribution were similar to those whose primary tumor was HER-2 ϩ .…”
Section: Correlation Of Her-2 Gene Status Between Ctcs and Primary Tusupporting
confidence: 81%
“…Conventional pathological analysis and touch prep assays showed complete concordance with HER-2 and uPAR gene status in 21 and 7 consecutive patients, respectively, thereby validating the use of TPs for this purpose (P ϭ 0.0001). Similar results were obtained with HER-2 gene status of CTCs and pathological analysis of primary tumors provided acquisition (i.e., clonal selection͞ expansion) of HER-2 gene amplification in CTCs associated with cancer progression was taken into consideration (19). Expression of HER-2 protein in 52 cases using either their primary tumors or CTCs showed a minimum of 96% concordance with HER-2 gene amplification determined by the pathologist.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Previous studies have demonstrated that cytokeratin/HER2 double-positive clustered peripheral blood cells have a high potential for locomotion suggesting that they might be precursor cells responsible for the development of DTCs [12]; furthermore, HER2-positive CTCs have a growth and survival advantage [12]. In addition, it has been shown that HER2 gene amplification can be acquired during breast cancer progression [26]. This hypothesis is further supported by the recently reported 14% discordance of HER2 overexpression between the primary tumor and the corresponding metastases in patients with breast cancer [27].…”
Section: Discussionmentioning
confidence: 99%
“…Another recently published study also showed that HER2 amplification was more frequently observed in circulating cells than in primary tumours and therefore concluded that HER2 amplification could be acquired during the metastatic process (Meng et al, 2004). The HER2 amplicon corresponds to a 280-kb minimal region of amplification at the HER2 locus of chromosome 17q arm, in breast cancer.…”
Section: Discussionmentioning
confidence: 93%